Effect of spray dryer settings on the morphology of illite clay granules (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Spray drying is an effective and common method for powder drying, e.g. clay. The morphology and properties of spray dried granules depend on properties of slurry and operational conditions of spray dryer. The aim of this study was to investigate the effect of spray dryer settings on the morphology of illite clay granules. Laboratory scale spray dryer was used. Operational conditions: inlet temperature 190-220˚C, outlet temperature 70-96˚C, spray dispersion is obtained using two-fluid nozzle where the slurry feed was varied from 4.5 to 15 ml/min and gas pressure 15-40 mm. Slurry was prepared from clay fraction under 2 µm without additives. Latvian illite clay from Iecava, Pavāri and Laža deposits was studied. Slurries with concentration 1, 8 and 15 mass% was used.The size and morphology was investigated by scanning electron microscopy, surface area and porosity by liquid nitrogen sorption.All obtained granules irrespective of spray dryer settings were well-rounded and dense without large pores or holes, however the surface was rough. The mean diameter of granules was in range of 2.6-5.4 µm, depending on slurry feed rate. The surface area of produced granules mostly depended on clay composition and was in a range of 70-92 m2/g. Inlet temperature in a range of 190-220 °C was found to be appropriate to produce well dried clay granules (moisture content <10 wt%).